2014
DOI: 10.1007/s10162-014-0472-x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Noise-Induced Hearing Loss in 129S6 and MOLF Mice: Identification of Independent, Overlapping, and Interacting Chromosomal Regions

Abstract: Noise-induced hearing loss (NIHL) is a prevalent health risk. Inbred mouse strains 129S6/SvEvTac (129S6) and MOLF/EiJ (MOLF) show strong NIHL resistance (NR) relative to CBA/CaJ (CBACa). In this study, we developed quantitative trait locus (QTL) maps for NR. We generated F1 animals by intercrossing (129S6×CBACa) and (MOLF×CBACa). In each intercross, NR was recessive. N2 animals were produced by backcrossing F1s to their respective parental strain. The 232 N2-129S6 and 225 N2-MOLF progenies were evaluated for N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…2; Shao et al 2010;Yazbek et al 2011;DeSantis et al 2013;Kato et al 2014;Winawer et al 2014;Zhu and Matin 2014). The CSSs and congenic strains derived from CSSs have been used to map QTLs and identify causal genetic variants for traits such as body weight, glucose homeostasis, anxiety, hearing loss, bone morphology, blood clotting, liver fibrosis, energy expenditure, seizure susceptibility, among others (Singer et al 2004;Singer 2005;Winawer et al 2007;Gregorová et al 2008;Sa et al 2008;Shao et al 2008;Boell et al 2011;DeSantis et al 2013;Spiezio et al 2014;Street et al 2014). …”
Section: Chromosome Substitution Strains (Csss)mentioning
confidence: 99%
See 1 more Smart Citation
“…2; Shao et al 2010;Yazbek et al 2011;DeSantis et al 2013;Kato et al 2014;Winawer et al 2014;Zhu and Matin 2014). The CSSs and congenic strains derived from CSSs have been used to map QTLs and identify causal genetic variants for traits such as body weight, glucose homeostasis, anxiety, hearing loss, bone morphology, blood clotting, liver fibrosis, energy expenditure, seizure susceptibility, among others (Singer et al 2004;Singer 2005;Winawer et al 2007;Gregorová et al 2008;Sa et al 2008;Shao et al 2008;Boell et al 2011;DeSantis et al 2013;Spiezio et al 2014;Street et al 2014). …”
Section: Chromosome Substitution Strains (Csss)mentioning
confidence: 99%
“…For example, a double CSS, which combined substituted Chromosomes 2 and 6, synergistically increased airway hyperresponsiveness (Ackerman et al 2005). Another example involves noise-induced hearing loss in CSSs and congenic strains derived from 129S6/SvEvTac and CBA/CaJ (Street et al 2014). Although QTLs were mapped to Chromosomes 4 and 17 with CSSs, subsequent studies with congenic strains and CSS crosses revealed both inter-and intrachromosomal epistatic interactions that regulated hearing loss.…”
Section: Epistasismentioning
confidence: 99%
“…The phl1 locus on proximal Chr 17 and the ahl3 locus on distal Chr 17 are in the same regions that were shown on 129S6 mouse to have nr1 and nr6 loci, respectively (Street et al 2014). In light of this evidence, we speculated whether the AHL phenotype in 129S6 mice is genetically linked to the NR loci of Chr 17.…”
Section: Introductionmentioning
confidence: 87%
“…The strongest statistical association with NR was found on Chr 17, indicating that genes in these regions are most likely to contribute to the NR phenotype. Chr 17 was linked to two loci, nr1 on proximal Chr 17 (between markers D17Mit143-D17Mit100) and nr6 on distal Chr 17 (between markers D17Mit119-D17Mit1) (Street et al 2014). Independently, other research has shown that these genomic regions were also associated to other AHL genes (Mashimo et al 2006;Nemoto et al 2004).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation